Relevansi Keteladanan Guru dalam Pembentukan Karakter Siswa yang Religius - Rohani, Aryawan Efendi; Sileuw, Marwan; Iribaram, Suparto (Tapis: Jurnal Penelitian Ilmiah, 2023)
As an educator, the teacher’s attitude and behavior are often played as role models for students. Unfortunately, there were few studies discussed this context and only focus on the process of object-based values formation, so that the teacher's qualifications as a subject tend to be neglected in scientific discussions. This study focuses on "How is the relevance of teachers exemplary in the process of forming religious student characters". To answer this question, this study uses a descriptive qualitative approach by conducting structured observations and interviews with school principals and teachers. This study revealed that the formation of teachers' attitudes and behaviors as educators are very important in shaping students' characters to become more religious in addition to an intensive communication process.